A NEW COMBINATION IN PSEUDERANTHEMUM (ACANTHACEAE) - Turner, Ian (Research Center for Biology, 2018)
TURNER, I. M. 2018. A new combination in Pseuderanthemum (Acanthaceae). Reinwardtia 17(1): 55â57. â A new combination is provided in Pseuderanthemum for Eranthemum diantherum Roxb., an Acanthaceae species from the Moluccas. Pseuderanthemum depauperatum Merr. is a synonym of Pseuderanthemum diantherum. Lectotypes for Eranthemum diantherum and Pseuderanthemum depauperatum are designated.